The transcriptome of zinc deficient maize roots and its relationship to DNA methylation loss - Svenja Mager; Brigitte Schönberger; Uwe Ludewig (BMC Plant Biology, 2018)
Abstract Background Zinc (Zn) is an essential micronutrient of all organisms. Deficiency of zinc causes disturbance in crucial plant functions, as a high number of enzymes, including transcription factors, depend on zinc for proper performance. The plant responses to zinc deficiency are associated with increased high affinity Zn uptake and translocation, as well as efficient usage of the remaining zinc, but have not been characterized in molecular detail in maize. Results The high affinity transporter genes ZmZIP3,4,5,7 and 8 and nicotianamine synthases, primarily ZmNAS5, were identified as primary up-regulated in maize roots upon prolonged Zn deficiency. In addition to down-regulation of genes encoding enzymes involved in pathways regulating reactive oxygen species and cell wall-related genes, a massive up-regulation of the sucrose efflux channel genes SWEET13a,c was identified, despite that in –Zn sugar is known to accumulate in shoots. In addition, enzymes involved in DNA maintenance methylation tended to be repressed, which coincided with massively reduced DNA methylation in Zn-deficient roots. Reduced representation bisulfate sequencing, which revealed base-specific methylation patterns in ~ 14% of the maize genome, identified a major methylation loss in -Zn, mostly in transposable elements. However, hypermethylated genome regions in –Zn were also identified, especially in both symmetrical cytosine contexts. Differential methylation was partially associated with differentially expressed genes, their promoters, or transposons close to regulated genes. However, hypomethylation was associated with about equal number of up- or down-regulated genes, questioning a simple mechanistic relationship to gene expression. Conclusions The transcriptome of Zn-deficient roots identified genes and pathways to cope with the deficiency and a major down-regulation of reactive oxygen metabolism. Interestingly, a nutrient-specific loss of DNA methylation, partially related to gene expression in a context-specific manner, may play a role in long-term stress adaptation.